On the role of individuals in models of coupled human and natural systems: Lessons from a case study in the Republican River Basin. (June 2017) - Noël, Paul H.; Cai, Ximing
Abstract: In models of coupled human and natural systems (CHANS), the role of individuals and human behavior is often overlooked as data are scarce and assumptions hard to verify. To assess this role, we couple an agent-based model simulating farmers' behavior and a groundwater model and apply the models to the case of groundwater-fed irrigation in a river basin in the High Plains Aquifer region. Results show the crucial role of human behavior in driving the interactions between these coupled systems. Conversely, individuals are impacted by the systems' dynamics in different ways depending on physical, economic and social characteristics. The findings provide implications for local policy making and education and demonstrate that assumptions on human behavior could be treated as an additional source of uncertainty. This work suggests that modeling individuals and human behavior can be an important step to simulate and understand the dynamics of CHANS in a holistic way. Highlights: Individuals and human behavior play a crucial role in driving CHANS' dynamics. Modeling individuals shows how CHANS' dynamics impact these individuals differently. Assumptions on human behavior have considerable effects on model results. Education and information diffusion can have critical roles in water conservation.